Compositional Meanings of the New Normal Protocol Signs: A Case Study at Sanur Port, Bali - Ni Made Ayu Widiastuti; Ketut Artawa; I Wayan Mulyawan (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims at identifying the types of new normal protocol signs placed at Sanur Port, Denpasar City, Bali Province, and analyzing the compositional meanings of the signs based on the linguistic landscape approach. The outdoor public signs at Sanur Port, Denpasar City, Bali-Indonesia were the source of data in this study. All types of outdoor signs were taken in a specific given territory marked by two gates of entrances to access Sanur Port, the Northern gate on Matahari Terbit Street and the Southern gate on Hangtuah Street. The public signs were collected by the documentation method. The photos were taken in November 2021 by the researchers. The data in this study were analyzed qualitatively based on the multimodal approach, specifically the compositional meanings since the new normal protocol signs were possibly viewed from the social semiotic visual displays. The information value, framing, and salience are the parts of the analysis. The results show that there were nineteen outdoor signs related to health protocols in the new normal situation placed at the Sanur Port area categorized into two types, they are the government and private signs with the dominant language used was Indonesian. The government public signs were dominantly placed around the area of the Southern Gate. It was related to the social condition in which a long time ago that Gate was the main entrance to enter Sanur Beach, and the ticketing desks were placed nearby the Southern Gate, despite the fact that the parking lots are larger in the Northern Gate area. Two private signs were permitted to be placed at the Sanur Port, even though there were only four locations as the placement of the wash basin with the verbal messages. It is considered that they had the permission from the authority of Sanur Port and Sanur Village as they gave contribution to the village.